Performance and morfhometric characteristics of Santa Inês sheep and Texel x Santa Inês lambs on pasture - Rodrigues Moreira , Yara; Ramalho Haddade , Ismail; Chambela Neto , Alberto; Deminicis, Bruno Borges; Gomes da Silveira Deminicis, Renata; Margon Zanetti , Letícia (Scientia Agraria Paranaensis, 2022)
Brazilian sheep farming has been gaining prominence with the increase in meat production, seeking more efficiency and profitability. Thus, the creation of the Santa Inês breed has stood out, as it is highly adaptable to different types of environments and has potential for meat production. The objective of this study was to evaluate the performance characteristics of the morphometric sheep of the Santa Inês breed, recently-Paris, with their respective lamb Texel x Santa Inês, a paste, in creep feeding system. For this purpose, 30 Sheeps and theirs and the respective lamb were used for natural breastfeeding for 60 days until weaning. The randomized blocks used, with two treatments (absence of the presence of the private feeder), with 10 repetitions, being shadow sheep by repetition municipality or relative lamb. In studies on the termination of two lambs, the bone of heavy animals was measured at the beginning and at the end of the experiments (25 days), using the 30-lambs weaned. The randomized blocks, used with three treatments (0, 400 and 800 g of concentrate/lamb/day). There was no difference in weight between the sheep outside of lamb (supplemented or not). There were no two treatments effect on the morphometric characteristics among the sheep outside between the lamb bone. The use of creep feeding to supplement lambs kept on natural lactation does not provide weight gain in sheep, nor does it provide weight gain in supplemented lambs. Lamb supplementation does not influence the morphometric characteristics of ewes and lambs during lactation. Private supplementation during breastfeeding does not increase lambs’ weight gain until weaning, but food supplementation, via creep feeding with 400 g/animal/day, in the finishing phase presents the best results for weight gain.